The Role of Education within a Knowledge Based Society: Teachers’ Perception on how e-Learning Systems can be integrated in Classroom Activities - Eftimie, Raluca Cristina (Journal of Education and Vocational Research, 2012)
The development of the interactive, collaborative and dynamic e-learning methods is considered the primary mode of evolution of the Romanian and international educational systems. Most of the studies have revealed the widespread benefits of these technologies and exemplifying their applicability and their evolution within the education systems. However, few studies clearly identify the role that e-learning platforms have in the improvement of teaching - learning and how these technologies can be integrated into the classroom. This article proposes a new approach related to the integration of these systems while providing educational acts, starting by identifying and understanding the perceptions that teachers have regarding this type of innovative technology, explaining and interpreting the results of a qualitative research conducted within Romanian educational market. Teacher’s perception on the role of e-learning education is interpreted as a factor, which influences the quality of the use and the integration of these technologies in the Romanian educational environment, reaffirming the need for a coherent implementation of these instruments at a specific school level but also at general educational environment integration.